The temperature change along trajectories of process of equilibrium condensation of multicomponent mixtures. - A. K. Frolkova; L. A. Hahin; T. V. Chelyuskina; L. I. Chernyh (Тонкие химические технологии, 2008)
The temperature change along trajectories of process of open equilibrium condensation is investigated. The equation of temperature dependence along a trajectory of the open equilibrium condensation, similar to Schreinemakers`rule is received.